Single Executive in The Indonesian Presidential System - Sudirman, Sudirman (Magister of Law, Faculty of Law, University of Mataram, 2023)
This article discusses a single executive in the Indonesian presidential system. A single executive is power as head of state and power as head of government depends, on one hand, on the President. However, the 1945 Constitution does not explicitly discuss the concept of a single executive, so information about this concept is not collected properly, so this article discusses in depth the concept of a single executive in the Indonesian presidential system based on the 1945 Constitution. This study uses normative legal methods. The finding indicated that the single executive in the Indonesian presidential system was based on the 1945 Constitution, which can be seen from the position of the president hold the inherent power of a head of state; the chief of the army, holds the pardon power, making government regulations and presidential regulations; appointing and dismissing ministers; holding the administrative power; and holding the diplomatic power.